Tribunal of homebuyers claim: an effective and efficient dispute resolution to protect homebuyer / Yusri Md Yusub - Md Yusub, Yusri (Faculty of Architecture, Planning and Surveying, 2015)
All developing countries have its own a well and organized instruments related to land, housing and property development that is considered as part of the mechanism that will support the growth of those areas. A well and organized mechanism related to those areas will also contribute to the public confidence towards the property developers. In ensuring the rights of the purchasers are protected from any problems related to housing development, then a tribunal was formed and named as Tribunal for Homebuyers’ Claim which was established in the year 2002 under the Housing Development (Control and Licensing) Act, 1966. It is the objective of this dissertation to study on the effective and efficient of the tribunal towards protecting homebuyer’s rights base on the Housing Development (Control and Licensing) Act, 1966 and the Housing Development (Tribunal for Homebuyer Claims) Regulations, 2002.